Development of digital ecosystem and formation of digital platforms in Uzbekistan - Makhmudova Guljakhon; ASHUROV Zufar; RAZAKOVA Barno (Pi-Economy, 2022)
The current process of globalization poses the task of transition to a digital economy for developing states. For this task, the creation of a favorable digital economy ecosystem is a basic prerequisite. The digital economy of each country has a separate infrastructure or ecosystem. Each structural part of the ecosystem covers end-to-end digital technologies, such as mobile technologies, BigData, robotics, quantum technologies, cloud technologies, artificial intelligence, internet of things, virtual and augmented reality technologies, digital platforms. World experience shows that the digitalization of the economy is the most important condition for the socio-economic integration of countries. The practice takes into account a number of indicators, which show a picture of the digitalization of spheres and sectors of the country’s economy. This research work examines the need for the development of a digital ecosystem, the essence and indicators of e-government, analyzes the issues and trends of their development in the case of Single Portal of Interactive Public Services (SPIPS). In addition, the essence and trends of the ecosystem of the digital economy are revealed, in particular, the emphasis is placed on normative regulation by the government, the e-government indices are analyzed, and the features of the development of the digital ecosystem in Uzbekistan are specified. Based on the adopted statutory acts and the “Digital Uzbekistan-2030” Strategy, the scientific conclusions have been drawn for the further development of the digital ecosystem and e-government in the country. The purpose of the study is to reveal the trends and priorities of ecosystem of the digital economy of Uzbekistan, to present scientific and practical conclusions on practical significance of the SPIPS digital platform. In the process of research, we used structural and system approaches, classification method, logical method, scientific abstraction, and generalization method. The use of these methods in total enabled us to carry out a comprehensive analysis of the studied area, to make theoretical generalizations, to formulate practical recommendations and conclusions. Improvement of the quality and efficiency of the SPIPS is based on the development of the information and communication technology of the country and on the innovative literacy of citizens. In accordance with legislative acts, ensuring the quality public services and harmonization of the digitalization processes of the system for the provision of various public services are priority areas for reforming the e-government in Uzbekistan.